Keunikan Tari Barong Budaya Bali - Sallaby, Fikri; Saputra, Dosi Martin; Novrianto, Aldo; Putra, Qodri Amril Syah (Jurnal Dehasen Mengabdi, 2024)
Barong dance is one of Bali's cultural heritages that has high historical, spiritual and artistic values. This dance is not only an art performance, but also a symbol of protection and magical power in Balinese beliefs. This article aims to examine the uniqueness of Barong Dance from various aspects, including history, symbolic meaning, and performance techniques. Through a descriptive qualitative approach, this research analyzes the cultural elements contained in Barong Dance, such as costumes, musical accompaniment, dance movements, and accompanying rituals. The results show that the uniqueness of Barong Dance lies in its blend of dynamic performing arts and sacred spiritual functions, making it one of the most authentic representations of Balinese culture. This article also highlights the importance of Barong Dance preservation as an effort to maintain the sustainability of Balinese traditions and cultural identity in the midst of modernization.